2013
DOI: 10.4209/aaqr.2013.01.0006
|View full text |Cite
|
Sign up to set email alerts
|

Transported and Local Organic Aerosols over Fukuoka, Japan

Abstract: In order to understand transported and local pollution in an urban area that are strongly affected by long-range transport of air pollution, daily concentrations of 15 polycyclic aromatic hydrocarbons (PAHs) and 20 n-alkanes in the total suspended particles were simultaneously measured at sites in Western Japan on Fukue Island (FI), located downwind of mainland East Asia, and Fukuoka City (FC), a megacity close (< 200 km) to the FI site, in spring and winter 2010 and summer 2011. The average total PAH concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…6) In recent decades, emissions of air pollutants from mainland East Asia have unprecedentedly increased with the rapid economic growth 7) and long-range transport of air pollutants in East Asia has been reported in recent years. [8][9][10][11][12][13][14] The occurrence and transport of dust storms and anthropogenic air pollutants in East Asia have been monitored using satellite data and ground-based measurements in central Korea. 9,10) Kim et al 9) reported episodes of anthropogenic pollutant particles that arrived at the Korean peninsula from eastern China and indicated that the anthropogenic pollutant particles were largely detected in the form of smoke over the Yellow Sea region.…”
mentioning
confidence: 99%
“…6) In recent decades, emissions of air pollutants from mainland East Asia have unprecedentedly increased with the rapid economic growth 7) and long-range transport of air pollutants in East Asia has been reported in recent years. [8][9][10][11][12][13][14] The occurrence and transport of dust storms and anthropogenic air pollutants in East Asia have been monitored using satellite data and ground-based measurements in central Korea. 9,10) Kim et al 9) reported episodes of anthropogenic pollutant particles that arrived at the Korean peninsula from eastern China and indicated that the anthropogenic pollutant particles were largely detected in the form of smoke over the Yellow Sea region.…”
mentioning
confidence: 99%
“…In addition, data of the site on Tuoji Island in China, which were obtained simultaneously with our experiments through collaborative research, were included in the PMF to determine the effect of TAP. The CHAAMS, Fukue, Fukuoka, and Tuoji sites have been described in detail by Shimada et al (2015), Sato et al (2013), andZhang et al (2016). The sampling method for PM 2.5 and analytical method for PM 2.5 and metals were reported by Shimada et al (2015).…”
Section: Positive Matrix Factorizationmentioning
confidence: 99%
“…Numerous studies conducted in Japan (Kaneyasu and Takada, 2004;Tang et al, 2005;Ogawa et al, 2012;Sato et al, 2013) reported that PAHs were transported from China to Japan. Kaneyasu and Takada (2004) collected fine atmospheric aerosols from Miyako Island and Amami Island and analyzed their chemical components.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations